PENGARUH PERENCANAAN PAJAK, ARUS KAS INVESTASI DAN FIRM SIZE TERHADAP RETURN SAHAM (STUDI EMPIRIS PADA PERUSAHAAN SEKTOR PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2019 – 2023) - Gunawan; Pratiwi, Adhitya Putri (Publika Citra Media, 2025)
This research aims to determine the effect of tax planning, cash flow and Firm Size on stock Returns. The population in this research is all companies in the Properties & Real Estate sector listed on the Indonesia Stock Exchange (BEI) in the 2019-2023 period, a total of 92 companies. The type of research used is quantitative. Sample selection was carried out based on the purposive sampling method with samples obtained from 9 companies. The data analysis technique used is statistical analysis and panel data regression. By processing the data using the e-views 10 program. The research results show that Tax Planning has no significant effect on Stock Returns. Investment Cash Flow has a significant negative effect on Stock Returns and Firm Size does not have a significant effect on Stock Returns. So Tax Planning, Investment Cash Flow, and Firm Size simultaneously influence Stock Returns.